PERAN BELANJA NEGARA DALAM PROGRAM PENURUNAN STUNTING - Muhammad Heru Akhmadi; Iyas Theresia Pasaribu (Universitas Pakuan, 2020)
The allocation of state expenditures in the APBN or APBD is one of the determinants of achieving development goals in Indonesia. On the health function, government spending can accelerate the reduction of stunting. The government really hopes that the funds released can be optimally absorbed in accordance with the applicable payment mechanism. This research aims to see the role of government spending, through the Special Allocation Fund (DAK) scheme, reducing stunting in the province of North Sumatra in 2019. This research uses a qualitative method through a case study approach. The research location was conducted at the North Sumatra Provincial Health Office. The results showed that the performance of the absorption of Physical DAK in the health sector for the stunting reduction program reached 82.9% of the budget allocation. This absorption achievement was not optimal. Several things that affect the low performance are due to the mismatch of components in the Budget Implementation List (DPA) and in the KPPN KRISNA application. in terms of the fund management mechanism, it is in accordance with the regulations and there are no obstacles or problems in the implementation of spending. The results of this study are expected to provide an analysis of budget absorption to help map and improve the effectiveness of the output of activity programs and the application of the concept of value for money.